Global Energy Development and Climate-Induced Water Scarcity—Physical Limits, Sectoral Constraints, and Policy Imperatives - Christopher A. Scott; Zachary P. Sugg (Energies, 2015)
The current accelerated growth in demand for energy globally is confronted by water-resource limitations and hydrologic variability linked to climate change. The global spatial and temporal trends in water requirements for energy development and policy alternatives to address these constraints are poorly understood. This article analyzes national-level energy demand trends from U.S. Energy Information Administration data in relation to newly available assessments of water consumption and life-cycle impacts of thermoelectric generation and biofuel production, and freshwater availability and sectoral allocations from the U.N. Food and Agriculture Organization and the World Bank. Emerging, energy-related water scarcity flashpoints include the world’s largest, most diversified economies (Brazil, India, China, and USA among others), while physical water scarcity continues to pose limits to energy development in the Middle East and small-island states. Findings include the following: (a) technological obstacles to alleviate water scarcity driven by energy demand are surmountable; (b) resource conservation is inevitable, driven by financial limitations and efficiency gains; and (c) institutional arrangements play a pivotal role in the virtuous water-energy-climate cycle. We conclude by making reference to coupled energy-water policy alternatives including water-conserving energy portfolios, intersectoral water transfers, virtual water for energy, hydropower tradeoffs, and use of impaired waters for energy development.